Phytomedicine nanoformulations for Parkinson's disease - Chinthu V. Saji; K P Mohanakumar; Rajesh A Shenoi (Phytomedicine Plus)
Background: Current medications for Parkinson's disease (PD) primarily offer symptomatic relief, and often lead to adverse effects on long-term use. This highlights the need for disease-modifying therapies. In recent years, attentions of both clinicians and patients have shifted to herbal medicines that are rich source of bioactive compounds with therapeutic potential to target multiple pathways involved in PD pathology. When integrated with nanotechnology, phytomedicines can overcome key limitations of herbal molecules, such as poor solubility, low bioavailability, and difficulty in crossing the blood brain barrier (BBB). Methods: A literature survey was conducted using PubMed. Studies were categorized into in vitro and in vivo models of the disease for assessing their relevance and impact on PD research. Results: The review identified 26 nanoformulations from seven distinct herbal molecules and eight different whole plant extracts that have been evaluated for their effectiveness in treating PD and other brain disorders. In vitro studies demonstrated enhanced cellular uptake and neuroprotective effects, while in vivo models showed improved pharmacokinetics, BBB permeability and neuroprotective outcomes. Additionally, nine plant-derived compounds with potential effects against PD, but are not nanoformulated were investigated, highlighting their neuroprotective mechanisms but exposing the existing limitations. This article emphasizes the improved neuroprotective effects of nanoformulated herbal compounds in cellular and animal models of PD and outlines the mechanisms by which these nanoformulations enhance BBB penetration. Conclusions: Phytomedicines formulated using nanoliposomes, nanoemlusions, polymeric nanoparticles, nanocrystals and metal nanoparticles have shown promise in improving the drug bioavailability and BBB penetration, resulting in better therapeutic effect in PD cellular and animal models. However, challenges such as scalability, regulatory compliance, and concerns over long term safety of these nanoformulations have to be considered for them to be clinically viable. Hence addressing these issues through rigorous preclinical and clinical testing is essential to confirm their safety and therapeutic potential. Further advancements in PD treatment could be achieved by developing multicomponent herbal nanoformulations that act synergistically on multiple PD targets. This approach may be effective in addressing the underlying pathogenesis of PD, thereby slowing the disease progression.